Strategi Pembelajaran Pendidikan Agama Islam Berbasis Masalah - Wawan Setiawan; Ahmad Fauzan Akbar; Gusmaneli Gusmaneli (STIKes Ibnu Sina Ajibarang, 2024)
To prepare for the birth of the golden generation that will continue to relay the leadership of Indonesia in 2045 the government has been doing various things such as: the provision of teachers and human resources that meet the qualifications and competency requirements, curriculum development up to the level of the education (curriculum), development of facilities for educational infrastructure, increase education spending, education of ICT-based services and others. Other preparations to be able to produce the expected generation through character education. Already many are produced through these efforts, but also there are many things that have to be prepared. One is to prepare students to be the generation that has the ability to find a solution to real problems encountered in everyday life. For this purpose, the implementation of Problem-Based Learning Strategy (PBL) is abbreviated considered suitable for application in the learning activities in schools. Through PBL learners are trained to find solutions to the problems faced. In order for the application of PBL can be run as expected it is recommended that the Government (Ministry of Education and Culture) launched the implementation of PBL in learning activities in schools, train teachers in the implementation of PBL as well as support in the form of policies, budget and facilities/infrastructure. As the agency responsible for the field of ICT for education, Pustekkom advised to provide support in the form of ICT-based learning resources